GAMBARAN FUNGSI INTELEKTUAL LANJUT USIA DI KELURAHAN MOTOBOI BESAR, KECAMATAN KOTAMOBAGU TIMUR - Tjomo, Vika; Kristamuliana; Rompas, Sefti S. J (Universitas Sam Ratulangi, 2024)
Background: The elderly generally experience a decrease in functional capacity, one of which is a change in cognitive function, which results in a decrease in the intellectual function of the elderly. Of the 6 elderly people who were interviewed in Motoboi Besar Village, 5 forgot their date of birth and the